AUGMENTED ANNOTATIONS: INDOOR DATASET GENERATION WITH AUGMENTED REALITY - V. Saran; J. Lin; A. Zakhor (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
The proliferation of machine learning applied to 3D computer vision tasks such as object detection has heightened the need for large, high-quality datasets of labeled 3D scans for training and testing purposes. Current methods of producing these datasets require first scanning the environment, then transferring the resulting point cloud or mesh to a separate tool for it to be annotated with semantic information, both of which are time consuming processes. In this paper, we introduce Augmented Annotations, a novel approach to bounding box data annotation that solves the scanning and annotation processes of an environment in parallel. Leveraging knowledge of the user’s position in 3D space during scanning, we use augmented reality (AR) to place persistent digital annotations directly on top of indoor real world objects. We test our system with seven human subjects, and demonstrate that this approach can produce annotated 3D data faster than the state-of-the-art. Additionally, we show that Augmented Annotations can also be adapted to automatically produce 2D labeled image data from many viewpoints, a much needed augmentation technique for 2D object detection and recognition. Finally, we release our work to the public as an open-source iPad application designed for efficient 3D data collection.